Building Effective Rules and Routines: A Guide for Pre-Service Teachers in Classroom Management - Yolanda, Rizky; Hapisoh, Hapisoh; Khairani, Dina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Building an environment that is appropriate to learning requires effective classroom management. A crucial part of this process for pre-service teachers is comprehending and putting into practice defined guidelines and regular practices. Routines offer regularity, simplify everyday tasks, and reduce interruptions, while rules set rules for appropriate conduct and foster an environment of deference and order. These components work together to improve classroom efficiency, decrease behavioral problems, and encourage student participation. The article examines the value of routines and norms in classroom management, emphasizing useful tactics designed for aspiring educators. It highlights how crucial it is to create regulations in conjunction with kids in order to promote responsibility and compliance. It also emphasizes how routines must be flexible in order to accommodate different classroom dynamics while still being structured. The implementation of these ideas is demonstrated through real-world examples, guaranteeing that pre-service teachers may successfully modify them for use in a variety of educational settings. Pre-service teachers may construct a productive, well-run learning environment that benefits both instructors and students by being proficient in the creation and upkeep of rules and procedures.